The origin of upper Precambrian diamictites, northern Norway: a case study applicable to diamictites in general - Molén, Mats O. (Geologos, 2017)
Upper Precambrian diamictites in Varangerfjorden (northern Norway) have been examined for evidence of origin, whether glaciogenic, gravity flow or polygenetic. Studies of geomorphology, sedimentology and surface microtextures on quartz sand grains are integrated to provide multiple pieces of evidence for the geological agents responsible for the origin of the diamictites. The documented sedimentary and erosional structures, formerly interpreted in a glaciogenic context (e.g., diamict structure, pavements and striations) have been reanalysed. Field and laboratory data demonstrate that, contrary to conclusions reached in many earlier studies, the diamictites and adjacent deposits did not originate from glaciogenic processes. Evidence from macrostructures may occasionally be equivocal or can be interpreted as representing reworked, glacially derived material. Evidence from surface microtextures, from outcrops which are believed to exhibit the most unequivocal signs for glaciation, display no imprint at all of glaciogenic processes, and a multicyclical origin of the deposits can be demonstrated. The geological context implies (and no geological data contradict this) an origin by gravity flows, possibly in a submarine fan environment. This reinterpretation of the diamictites in northern Norway may imply that the palaeoclimatological hypothesis of a deep frozen earth during parts of the Neoproterozoic has to be revised.